The Application of Realistic Approach to Improve the Mathematical Problem Solving Abilities of Grade VIII at SMP Negeri 2 Tebing Tinggi - Gresi Yolanda Sihombing; Hasratuddin (Prodi Pendidikan Matematika FMIPA Universitas Negeri Medan, 2024)
The aim of this research is to improve mathematical problem solving ablity with realistic approach in the students of grade VIII at SMP Negeri 2 Tebing Tinggi. The design of this research is Class Action Research (PTK) that consists of 2 cycles. The material used in this research is probability material. The object of this research is students' mathematical problem solving ability by applying realistic approach to probability material. The subject ini this research were 36 students of grade VIII-7 at SMP Negeri 2 Tebing Tinggi. The results of this research are: (1) In the initial test, only 1 student (2,2%) achieved the classroom mastery and the average score of students’ ability is in the very low category. (2) In the Cycle I, there was an improvement, with 18 students (50%) achieved the classroom mastery and the average score of students’ ability is 64,5 with a level of ability in the low category. (3) In the Cycle II, there was further improvement, with 32 students (88,9%) achieved the classroom mastery and the average score of students’ ability is 83,1 with a level of ability in the high category. Thus, it can be concluded that the application of realistic approach can improve the mathematical problem solving ability